Pre-pandemic SARS-CoV-2-specific IFN-γ and antibody responses were low in Ugandan samples and significantly reduced in HIV-positive specimens - Nantambi, Hellen; Sembera, Jackson; Ankunda, Violet; Ssali, Ivan; Kalyebi, Arthur Watelo; Oluka, Gerald Kevin; Kato, Laban; Ubaldo, Bahemuka; Kibengo, Freddie; Katende, Joseph Ssebwana; Gombe, Ben; Baine, Claire; et al. (Frontiers in Immunology, 2023)
We investigated whether prior SARS-CoV-2-specific IFN- and antibody responses in Ugandan COVID-19 pre-pandemic specimens aligned to this population's low disease severity. We used nucleoprotein (N)-, spike (S)-, NTD-, RBD-, envelope-, membrane-, SD1/2-directed IFN- ELISpots, and an S- and N-IgG antibody ELISA to screen for SARS-CoV-2-specific cross-reactivity. HCoV-OC43-, HCoV-229E-, and SARS-CoV-2-specific IFN- occurred in 23, 15, and 17 of 104 specimens, respectively. Cross-reactive IgG was more common against the nucleoprotein (7/110, 15.5%; p = 0.0016, Fishers' Exact) than the spike (3/110, 2.72%). Specimens lacking anti-HuCoV antibodies had higher rates of pre-epidemic SARS-CoV-2-specific IFN- cross-reactivity (p-value = 0.00001, Fishers’ exact test), suggesting that exposure to additional factors not examined here might play a role. SARS-CoV-2-specific cross-reactive antibodies were significantly less common in HIV-positive specimens (p=0.017; Fishers' Exact test). Correlations between SARS-CoV-2- and HuCoV-specific IFN- responses were consistently weak in both HIV negative and positive specimens. These findings support the existence of pre-epidemic SARS-CoV-2-specific cellular and humoral cross-reactivity in this population. The data do not establish that these virus-specific IFN- and antibody responses are entirely specific to SARS-CoV-2. Inability of the antibodies to neutralise SARS-CoV-2 implies that prior exposure did not result in immunity. Correlations between SARS-CoV-2 and HuCoV-specific responses were consistently weak, suggesting that additional variables likely contributed to the pre-epidemic cross-reactivity patterns. The data suggest that surveillance efforts based on the nucleoprotein might overestimate the exposure to SARS-CoV-2 compared to inclusion of additional targets, like the spike protein. This study, while limited in scope, suggests that HIV-positive people are less likely than HIV-negative people to produce protective antibodies against SARS-CoV-2.